Home Stay Tourism in Nepal (Voice of Teacher, 2022)
Tourism is the world's fastest growing industry. Nepal is one of the most beautiful countries in the world with lofty snowcapped mountains and scenic, peaceful settings. It has varieties of tourism resources, places of natural beauty, historical and cultural monuments, art, architecture, and festival set which are the best attractions to the foreign visitors in Nepal. Among various tourists are attractions in Nepal. Chitlang is one of the most scenic tourist destinations in Nepal. It is a land of natural scenery, the richbio-diversity, peaceful environment, and the ethnic diversity, the rich and diverse culture which attract visitors. The general objective of the study is to explore tourism prospect of rural tourism home stay. The respondents were selected by purposive sampling method in case of home stay survey and simple random sampling procedure was used for survey of visiting tourists and households. The sample size is selected 10 home stay owners selected from 18 home stay, and 18 different types of tourists (internal and external), 12 in Local people in total sampled data was 40 total. The study is based both on secondary and primary data collection from municipality profile, reports and direct fill up the structure questionnaire. The number of foreign tourists is found very low according to the local people. Local people were found very much interested and devoted for promoting tourism in the study area but there seems lack of co-ordination among the government authorities and local promoters and also lack of fund. In conclusion it can be said that deserves potentiality of becoming one of the best rural tourism destinations of the country and home stay was very effective to promote tourism. Therefore, package programs and tourism advertisement seem necessary to develop as a rural tourist destination.